Does the leadership style influence the office politics in performance appraisal? Empirical study from Malaysian financial sector - Daud, Zulkiflee; Elsaman, Hosam Azat; Mutazam, Mazli; Sallehuddin, Mohd Rashdan; Haron, Nasiruddin; Abidin, Mohd Abidzar Zainol (Edelweiss Applied Science and Technology, 2024)
Employees play a pivotal role in the Malaysian financial industry, as this sector requires individuals capable of meeting the demands of the global financial market and enhancing Malaysia’s position as a leading international financial hub. Consequently, employees’ behavior and practices can significantly impact the institution’s reputation. Previous research has identified office politics as a detrimental factor in organizational performance, prompting this study to investigate the impact of leadership styles on organizational politics within the context of performance appraisal. A survey was conducted through the distribution of questionnaires among 274 officers and clerical staff, selected using proportionate stratified random sampling from a Malaysian government financial institution based in Kuala Lumpur. Of the distributed questionnaires, 105 were completed and deemed usable. The study identified three reliable dimensions of politics in performance appraisal: acquiring benefits, human relations, and control. In examining leadership styles, the study found that the integrative leadership style was the only reliable dimension. Correlation analysis revealed that integrative leadership style generally correlates significantly and negatively with politics in performance appraisal. Specifically, integrative leadership style had a significant negative impact on the human relations and control dimensions. Regression analysis further indicated that integrative leadership style significantly and negatively influenced only the control dimension of performance appraisal politics. The study discusses the implications of these findings for future research and practice, as well as the limitations of the current study.